Determinants of turnover intention in the private universities in Malaysia: a conceptual paper - Ainer, Chitra Devi; Subramaniam, Chandrakantan; Arokiasamy, Lawrence (EDP Sciences, 2018)
Turnover intentions in academic institutions has become one of the main concern of the management as surviving and achieving excellence is very much about having the knowledgeable and committed employee. Therefore, it is one of the main and foremost issue for a management of higher education institution to give important. There are many factors that influence an academician to have turnover intentions. Hence, this study’s focus was to investigate the relationship between role ambiguity, work-overload, work family conflict, co-workers warmth, co-workers competence and turnover intentions. The variables studied in this paper were analyse from a research framework. The finding of this study has been discussed on role ambiguity, work-overload, work family conflict, co-workers warmth, co-workers competence and turnover intentions. Conclusion has been drawn from the support of literature that states that the variables influences on turnover intentions. This paper’s finding provides valuable guidance for researcher and practitioners to overcome and improve the current mechanism to reduce turnover intentions. The research has also found few new paths for thinking on how to manage employees that having turnover intentions in any organizations.